2018
DOI: 10.1016/j.scog.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Hedonic response in neuroleptic-free youth at ultra high-risk for psychosis

Abstract: Hedonic response is preserved in schizophrenia. However, it is unclear whether this is also true in individuals meeting criteria for “prodromal” psychosis, who are considered to be at symptomatic high risk for developing the disorder. In this study, we examined neurophysiological and self-reported response to emotional stimuli in UHR (n = 23) and healthy control (CN: n = 30) participants who passively viewed pleasant, unpleasant, and neutral images for 500 ms while the electroencephalogram was recorded and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
4
25
2
Order By: Relevance
“…In contrast to some previous studies in CHR-P (19,20) and meta-analytic evidence for a reduced self-reported emotional experience in individuals with major depressive disorder compared to healthy controls (56), reductions of MET-EE and -EA were not linked to depressive psychopathology, but to SIPS negative symptoms in our sample. Moreover, lowest MET-EE scores for positive valences were found in individuals who had experienced APS in the past.…”
Section: Emotional Empathy In Individuals At Ultra-high Risk Of Psychcontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to some previous studies in CHR-P (19,20) and meta-analytic evidence for a reduced self-reported emotional experience in individuals with major depressive disorder compared to healthy controls (56), reductions of MET-EE and -EA were not linked to depressive psychopathology, but to SIPS negative symptoms in our sample. Moreover, lowest MET-EE scores for positive valences were found in individuals who had experienced APS in the past.…”
Section: Emotional Empathy In Individuals At Ultra-high Risk Of Psychcontrasting
confidence: 99%
“…Medical treatment in individuals with schizophrenia could hypothetically have influenced findings. Even though acute effects of antipsychotic treatment were not shown (71), the increase in emotional empathy in medicated individuals with schizophrenia might reflect a restorative effect compared to the neuroleptic-free prodromal phase (20). However, negative long-term effects of antipsychotics on other measures of empathy or frontal function in general cannot be excluded (13,(72)(73)(74).…”
Section: Limitationsmentioning
confidence: 99%
“…Alternatively, noncurrent emotional experience may be independently manifested with a decline of neurocognitive function from the putative prodromal phase of schizophrenia. As previous findings using self-reports [ 47 , 49 ] and psychophysiological measures of laboratory-based emotional experiences [ 49 ] were shown to be diminished in individuals at UHR for psychosis, unlike established schizophrenia, the aberrant tendency of noncurrent emotion would be linked to current emotional experiences during the prodromal phase.…”
Section: Discussionmentioning
confidence: 57%
“…Forth, we did not assess depressive and anxiety symptoms simultaneously. According to some recent studies [ 49 - 51 ], depressive and anxiety symptoms may affect emotional experience of individuals at UHR for psychosis. To the best of our knowledge, however, this is the first study to examine noncurrent emotional experience in individuals at UHR for psychosis concurrently using comprehensive measures of trait affectivity, hypothetical anhedonia, and retrospective anhedonia.…”
Section: Discussionmentioning
confidence: 99%
“…However, most previous investigations of emotional processing in at-risk populations have focused on responses to broad "pleasant" and "unpleasant" categories only e.g. 12,[20][21][22][23] . This approach assumes that stimuli within a broad category have the same motivational salience, which is not the case 1,24 , and does not allow for an understanding of how differences in reward and punishment values among different pleasant and unpleasant stimuli might influence responses.…”
mentioning
confidence: 99%